Post Cambridge Analytica Fallout: Observing Facebook Users Awareness Regarding Data Security - Timanta Tarigan, Jos; M. Zamza, Elviawaty (International Journal of Engineering and Technology, 2018)
In early 2018, Cambridge Analytica, a UK based political consulting group, was in the middle of the spotlight regarding its activity collecting Facebook usersâ€™ personal data. The data was harvested without usersâ€™ consent and was used to influence voter opinion to support a presidency campaign. This event triggered numerous movement aimed to inform and motivate the public to be concern of the use of their data in social media. However, whether these actions have raised the awareness of social media users is yet to be investigated. The objective of this paper is to harvest the awareness of social media users in Indonesia. Weâ€™ve performed a survey and collected answers from 312 responders who actively use social media in everyday life. The result shows that most of the responders have a low awareness regarding the event and its impact to social media industry. Over 24% of our responders have heard of the event and only 7% of the responders were able to describe the event correctly. Moreover, most of these users did not aware how their profile information in social media may be used to achieve commercial or political purpose by social media industry or collaborating third party without their consent.Â Â